COVID-19 and Food: Challenges and Research Needs - Knorr, Dietrich; Khoo, Chor-San H. (Frontiers in Nutrition, 2020)
The paper highlights several food and nutrition related challenges encountered during the COVID-19 pandemic, including food and water safety, supply chain disruptions, food and water insecurity, consumer and food behavior, mal- nutrition and nutrient intakes, food surveillance technology as well as potential post COVID-19 strategies. Its main objective is to stimulate robust scientific discussions on existing research gaps and to develop long term “exit strategies” to prepare for future pandemics